External Factors Affecting EFL Self-Concepts of Students in Two Drama Clubs - Arifah Mardiningrum (Eralingua: Jurnal Pendidikan Bahasa Asing dan Sastra, 2020)
The study focused on the external factors inside the drama clubs affecting the EFL self-concept. The current study used a Comparative Case Study (CCS) design to compare the EFL self-concepts in two drama clubs through six participants. The study was a qualitative study, and the data were collected through interviews. The interviews were transcribed, coded, and analyzed by presenting the finding per drama club and then comparing between the two.  The external factors affecting the EFL self-concept in Drama Club 1 were comparison to peers’ English skills, people perceived as more competent in English, feedbacks from senior members and lecturer(s), play rehearsals, and on-stage performances. Meanwhile, the external factors in Drama Club 2 were preparation, feedback from peers and/or seniors, play-script, on-stage performances, feedback from a lecturer, and audiences’ identity. Comparatively, the factors found hold some similarities in that significant others, their feedbacks, and the activities prior to and during the play had certain roles in affecting the participants’ self-concepts. Meanwhile, the two clubs differ in the number of specific activities and the attitude that resulted from the presence and absence of a teacher figure